Wound complications following vulvar excision for nonmalignant lesionsAJOG Global Reports at a Glance - Glenn P. Boyles, MD; Ashlee M. Weaver, MD; David E. Cohn, MD; Floor J. Backes, MD; Larry J. Copeland, MD; Kristin L. Bixel, MD; Jeffrey M. Fowler, MD; David M. O'Malley, MD; Casey M. Cosgrove, MD (Elsevier, 2021)
BACKGROUND: There is a paucity of literature regarding the outcomes following vulvar excision for nonmalignant lesions. This is a common procedure among gynecologists and gynecologic oncologists, and a body of evidence is warranted to guide clinical care and future research. OBJECTIVE: This study aimed to estimate the rate of wound complications following simple vulvar excision and to identify the risk factors for these outcomes. Our secondary objectives were to determine the rates of (1) positive margins and (2) occult carcinoma in the cases of vulvar dysplasia. STUDY DESIGN: We conducted a single-institution, retrospective cohort study of the patients who underwent simple vulvar excision procedures for suspected premalignant or benign lesions between June 2016 and February 2020. Our primary outcome was the rate of composite wound complications, including wound separation or breakdown, infection, or hematoma. Our secondary outcomes were the incidence of (1) margins positive for residual dysplasia and (2) occult minimally invasive carcinoma. The Fisher exact tests and chi-squared tests were used to compare the categorical variables and logistic regression models and independent student t tests were used for continuous variables, as appropriate. Multivariate stepwise selection and multiple logistic regression was performed to evaluate the risk factors for complications and generate the odds ratios. RESULTS: Of the 338 patients included in the study, 143 (42.3%) experienced wound complication. Most of these complications were wound separation or breakdown (n=134, 39.6%), followed by infection (n=22, 6.5%), and hematoma (n=4, 1.2%). On multivariate analysis, the presence of high-grade vulvar dysplasia (adjusted odds ratio, 1.83; 95% confidence interval, 1.06-3.15), longer specimen diameter (adjusted odds ratio, 1.03; 95% confidence interval, 1.01-1.05), and lesion location on the perineum (adjusted odds ratio, 2.25; 95% confidence interval, 1.38-3.66) were independent risk factors. With high-grade vulvar dysplasia, the rate of positive margins was 50.2% (114/227) and that of occult microinvasive carcinoma was 17.2% (39/227). Notably, the primary and secondary outcomes were similar among gynecologic oncologists and gynecologists. CONCLUSION: Wound complications following vulvar excision for nonmalignant lesions are common. Select groups may benefit from anticipatory counseling and future interventional studies to prevent complication. The incidence of positive surgical margins and occult minimally invasive carcinoma is also high, reflecting the challenging nature of treating vulvar disease.